1997
DOI: 10.1143/jjap.36.5253
|View full text |Cite
|
Sign up to set email alerts
|

Initial Stage and Growth Process of Ceria, Yttria-Stabilized-Zirconia and Ceria-Zirconia Mixture Thin Films on Si(100) Surfaces

Abstract: Initial stages and growth processes of ceria ( CeO2), yttria-stabilized-zirconia (YSZ) and ceria-zirconia mixture ( Ce·ZrO2) thin films on Si(100) surfaces were studied in conjunction with O2 pressure. We showed that (110)-oriented films of CeO2, YSZ and Ce·ZrO2 grew obeying the arrangements of Si atoms in (2×1) or (1×2) structures on a Si(100) surface under about 5×10-7 Torr O2 gas at about 900° C. On the other hand, under 1×10-5 Torr O2 gas, (111)-oriented CeO2 polycrystal films gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…[1][2][3][4][5][6][7] It has several excellent properties: a relatively highdielectric constant (∼25, so-called high-K material), an interdiffusion barrier, low-leakage current, a wide band gap (∼5.6 eV), an adequate band offset with Si (1.4 eV), thermal and chemical stability, epitaxial growth on a Si substrate, and others. [1][2][3][4][5][6][7] It has several excellent properties: a relatively highdielectric constant (∼25, so-called high-K material), an interdiffusion barrier, low-leakage current, a wide band gap (∼5.6 eV), an adequate band offset with Si (1.4 eV), thermal and chemical stability, epitaxial growth on a Si substrate, and others.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] It has several excellent properties: a relatively highdielectric constant (∼25, so-called high-K material), an interdiffusion barrier, low-leakage current, a wide band gap (∼5.6 eV), an adequate band offset with Si (1.4 eV), thermal and chemical stability, epitaxial growth on a Si substrate, and others. [1][2][3][4][5][6][7] It has several excellent properties: a relatively highdielectric constant (∼25, so-called high-K material), an interdiffusion barrier, low-leakage current, a wide band gap (∼5.6 eV), an adequate band offset with Si (1.4 eV), thermal and chemical stability, epitaxial growth on a Si substrate, and others.…”
Section: Introductionmentioning
confidence: 99%
“…In the course of the investigation on the epitaxial growth of CeO 2 layers on Si substrates, [1][2][3][4][5][6][7][8][9][10][11][12] it was found that although high-quality CeO 2 ͑111͒ layers grow on Si͑111͒ substrates at low temperatures, such as room temperature, 7 200°C, 3 and 300°C, 8 CeO 2 layers grown on Si͑100͒ substrates have a ͑110͒ orientation and require a substrate temperature of ϳ820°C. Low-temperature processes are strongly desired for microelectronic applications, such as miniaturized stable capacitors, silicon-on-insulator structures, and buffer layers between high-temperature superconductors and substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Many attempts have been tried to obtain good quality YBa 2 Cu 3 O 7-x (YBCO) films on Si substrates, with the aim of taking advantage from the properties of both materials, but interdiffusion reactions and a poor lattice and thermal expansion coefficient matching require the use of a buffer layer at the semiconductor/superconductor interface. Yttria-stabilized zirconia (YSZ), Y 2 O 3 , MgO, SrTiO 3 , CeO 2 and their combinations have been proposed and used as buffer layers in the case of Si/YBCO systems [4][5][6][7][8][9][10]. In this paper we will present results concerning the deposition and the study of Si/buffer-layer system, when conventional substrates, magnetron sputtering technique and post-deposition annealing treatments are employed.…”
mentioning
confidence: 99%